2015
DOI: 10.1016/j.vaccine.2015.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Health communication and vaccine hesitancy

Abstract: Health communication is an evolving field. There is evidence that communication can be an effective tool, if utilized in a carefully planned and integrated strategy, to influence the behaviours of populations on a number of health issues, including vaccine hesitancy. Experience has shown that key points to take into account in devising and implementing a communication plan include: (i) it is necessary to be proactive; (ii) communication is a two-way process; (iii) knowledge is important but not enough to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
171
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(182 citation statements)
references
References 13 publications
4
171
1
6
Order By: Relevance
“…In a recent randomized-controlled trial, Glanz et al (2017) found that web-based information delivered on vaccines via social media platforms during pregnancy can have a positive impact on parental vaccine decisions [41]. However, communication strategies on immunization via social media are still not well understood and caution must be used to prevent legitimizing vaccine hesitancy [42]. Social media can be an important communication tool for public health, however the content of online debates needs to be better monitored to identify the predominant themes, the type of misinformation or specific requests for information, and to understand the current determinants among Canadian parents [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized-controlled trial, Glanz et al (2017) found that web-based information delivered on vaccines via social media platforms during pregnancy can have a positive impact on parental vaccine decisions [41]. However, communication strategies on immunization via social media are still not well understood and caution must be used to prevent legitimizing vaccine hesitancy [42]. Social media can be an important communication tool for public health, however the content of online debates needs to be better monitored to identify the predominant themes, the type of misinformation or specific requests for information, and to understand the current determinants among Canadian parents [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, communication strategies on immunization via social media are still not well understood and caution must be used to prevent legitimizing vaccine hesitancy [42]. Social media can be an important communication tool for public health, however the content of online debates needs to be better monitored to identify the predominant themes, the type of misinformation or specific requests for information, and to understand the current determinants among Canadian parents [42,43]. This study adds to this body of research and highlights the major themes in one online debate, as well as the need for ongoing monitoring due to the extent of misinformation being shared.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Dubé and others, listening to and determining the factors underlying delay or refusal are critical first steps at the individual and program level (9)(10)(11). Communication and intervention strategies must be tailored to address the problem.…”
Section: Addressing Vaccine Hesitancymentioning
confidence: 99%
“…Les efforts futurs de la santé publique en faveur de la vaccination doivent tirer parti des possibilités qu'offrent Internet et les médias sociaux et promouvoir d'une manière proactive l'importance et l'innocuité des vaccins, plutôt que d'adopter une approche réactive pour contrer les arguments des activistes anti-vaccination (47,50,51). En raison du rôle des médias sociaux dans l'hésitation à la vaccination, il importe d'élaborer des stratégies appropriées de communication en ligne.…”
Section: Que Peut-on Faire?unclassified